Difficult group goal improves serve reception of experienced volleyball players - Nogueira Dutra, L.; Novellino Benda, R.; Menezes Lage, G.; Ugrinowitsch, H. (Journal of Human Sport & Exercise, 2017)
This study investigated the effects of group goals difficulty on volleyball jump topspin serve reception with 36 experienced volleyball players. The volunteers performed an initial evaluation, whose results were organized in accordance to the level of performance and them divided into three similar groups: no goal, 10% and 30% group goal difficulty. Volunteers performed 810 receptions divided in 10 sessions during acquisition phase whose performance was scored from zero to 14 points. On retention test, the 30% of goal difficulty showed higher performance accuracy than 10% or no goal at all.